1992
DOI: 10.2331/suisan.58.2283
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Yolk Protein from the Scallop Ovary.

Abstract: A female specific protein (FSP) was identified and purified from the ovary of the Japanese scallop Patinopecten yessoensis by immunological techniques and a combination of precipitation with distilled water, ammonium sulfate fractionation, hydroxylapatite chromatography, and gel filtration. The molecular mass was determined to be approximately 450kDa. Three other female specific proteins, two with the same molecular mass and the other with 700kDa, showed different electrophoretic mobility from each other on na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 2 publications
1
14
0
3
Order By: Relevance
“…Les Vg sont des protéines de haut poids moléculaire (>400 kda) constituées d'hydrates de carbone, de lipides, de phosphates labiles en milieu alcalin dites alkali labile phosphates, de calcium et de zinc que l'on retrouve dans les tissus de gonades de bivalves (OSADA et al, 1992;SUZUKI et al, 1992). En juin 1998, nous avons récolté des myes provenant du site de référence ASE et des sites BE et ASJ (voir Figure 1 et Tableau 1 pour leur emplacement et caractéristiques pollutionnelles), afin de tester l'hypothèse selon laquelle les niveaux des constituants de la Vg pourraient être altérés par la présence de contaminants.…”
Section: Gauthier-clerc Et Al 2002unclassified
“…Les Vg sont des protéines de haut poids moléculaire (>400 kda) constituées d'hydrates de carbone, de lipides, de phosphates labiles en milieu alcalin dites alkali labile phosphates, de calcium et de zinc que l'on retrouve dans les tissus de gonades de bivalves (OSADA et al, 1992;SUZUKI et al, 1992). En juin 1998, nous avons récolté des myes provenant du site de référence ASE et des sites BE et ASJ (voir Figure 1 et Tableau 1 pour leur emplacement et caractéristiques pollutionnelles), afin de tester l'hypothèse selon laquelle les niveaux des constituants de la Vg pourraient être altérés par la présence de contaminants.…”
Section: Gauthier-clerc Et Al 2002unclassified
“…Osada et al (1992) and Suzuki et al (1992) suggested that the lipovitellin is synthesized within the oocytes. Recently, Lee et al (1996) The constitutive and inducible forms of hsp 70 appear to be functionally similar, with the induction of the heat shock response regulating the total pool of hsp 70 in the cell .…”
Section: Comparison Of Sds-page Gels (Not Shown) Of Hemolymph Frommentioning
confidence: 99%
“…yessoensis [1,3], but analysis of the Vtg gene expression by in situ hybridization has clarified it to occur in the ovarian follicle cells in C. gigas [7] and H. discus hannai [10], or auxiliary cells (equivalent to the ovarian follicle cells) in P. yessoensis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Purification of the Vn revealed it to be a large molecule ranging from 700 kDa to 450 kDa in its native form and composed of several subunits [1,3,4]. The Vn is synthesized as a precursor molecule, vitellogenin (Vtg), and processed by proteases into a mature molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation